2010
DOI: 10.1097/cnq.0b013e3181d912d8
|View full text |Cite
|
Sign up to set email alerts
|

Self-transcendence and Work Engagement in Acute Care Staff Registered Nurses

Abstract: The ability of human beings to find meaning by being directed toward something, or someone, other than themselves is termed "self-transcendence." Previous research indicated that the ability of nurses to self-transcend and thus derive positive meaning from patient-caring experiences increased work commitment and fostered work engagement. However, the relationship between self-transcendence and work engagement had not been investigated. The purpose of this study was to explore the levels and relationships of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 30 publications
5
32
0
4
Order By: Relevance
“…Age was the most commonly examined demographic factor (n=8 studies) with equivocal results (Cadiz, 2010;Giallonardo et al, 2010;Laschinger et al, 2012;Palmer et al, 2010;Rivera et al, 2011;Sullivan Havens et al, 2013;Walker & Campbell, 2013). Three studies reported a positive relationship between years of nursing experience and work Page 23 of 72 A c c e p t e d M a n u s c r i p t 23 engagement (Bamford et al, 2013;Palmer et al, 2010;Rivera et al, 2011) and one study reported no statistical significance .…”
Section: Demographic Variablesmentioning
confidence: 91%
“…Age was the most commonly examined demographic factor (n=8 studies) with equivocal results (Cadiz, 2010;Giallonardo et al, 2010;Laschinger et al, 2012;Palmer et al, 2010;Rivera et al, 2011;Sullivan Havens et al, 2013;Walker & Campbell, 2013). Three studies reported a positive relationship between years of nursing experience and work Page 23 of 72 A c c e p t e d M a n u s c r i p t 23 engagement (Bamford et al, 2013;Palmer et al, 2010;Rivera et al, 2011) and one study reported no statistical significance .…”
Section: Demographic Variablesmentioning
confidence: 91%
“…There is limited nursing work engagement literature available (Palmer, 2008;Simpson, 2009 frequency level of the 'not in the patient's best interest' subscale. In reference to this subscale, there was one known previously published research finding.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…The proposed relationships between current and additional study variables will be examined. According to Palmer (2008), for example, Self-Transcendence demonstrated a significant positive relationship with work engagement. This variable, in addition to nurses' age and years of experience, may be examined to refine the theoretical model 159 presented in this dissertation.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%
“…Hay estudios que revelan que hay una relación entre el nivel de auotrascendencia y el compromiso de la enfermera, manifestándose como una correlación positiva y significativa, entre ambos aspectos. Las enfermeras con un nivel mayor de auotrascendencia desarrollan y muestran mayores niveles de energía y son más absortas en su trabajo (Palmer, Quinn Griffin, Reed, & Fitzpatrick, 2010).…”
Section: Antecedentes En Enfermería Y El Adulto Mayorunclassified
“…(Reed, 1992;Reed, 2003). Se ha usado en estudios con adultos mayores deprimidos en edad avanzada, así como la relación entre autotrascendencia y actividades de la vida diaria en personas en sus propios hogares (Hoshi, 2008;Palmer et al, 2010). En otros estudios como en pacientes con VIH o SIDA, demostrando relación positiva entre bienestar y autotrascendencia (McCormick, Holder, Wetsel, & Cawthon, 2001;Mellors, Erlen, Coontz, & Lucke, 2001).…”
Section: Indicadores Empiricos Del Con-ceptounclassified